Evaluating and Comparing the Views of Teachers and Students about the Criteria of a Good Professor at Mashhad University of Medical Sciences Iran - Mohamad-Reza Darabi; Akbar Derakhshan; Mohamad-Ali Kiani; Gholam-Hosein Maleki; Masumeh Saeidi (Kerman University of Medical Sciences, 2014)
Background & Objective: The main goal of university includes educating specialists needed for society promotion and development of the knowledge developing research and providing the background for society development Undoubtedly professor is one of the main and effective factors in high education quality and training specialist workers requires strong faculty members that are experienced and skilled in various educational courses We decided to utilize two professor and student groups opinions about the indices of a good university teacher   Methods: In this descriptiveanalytic and crosssectional research 240 professors and 899 students of Mashhad University of Medical Sciences Iran were selected by hierarchical and simple random sampling methods The data were gathered by a researchermade valid and reliable questionnaire   Results: Teachers Characteristics for a good professor were respectively: Scholarships communication skills teaching skills evaluation skills and Physical characteristics and appearance of the teachers Students Characteristics for a good professor were respectively: communication skills Scholarships teaching skills evaluation skills then Physical characteristics and appearance of the teachers In the professors ANOVA test showed there was a significant relationship between the work experience rank and social field study of teachers and Priority communication skills scholarship teaching methods evaluation and faculty characteristics (p